Tourism in India / Gursharan Jeet Kaur and Gopal Kumar Johar - Kaur, Gursharan Jeet; Johar, Gopal Kumar (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2010)
In 1947, immediately after independence, the focus of development in India was on key areas like agriculture, housing, industry, irrigation, infrastructure and other social sectors. So in the field of tourism, India has been a late starter and has started getting attention in the last two decades only. The phenomenal explosion of international and domestic tourism is an inevitable by-product of the prosperity that India has achieved in recent times. It been duly recognized in National Tourism Policy, 2002 that Tourism not only generates employment but also upgrades human skills. The infrastructure created for Tourism can be used by all other sectors of the economy. Therefore, development of Tourism must not be viewed in isolation and the states must adopt an integrated approach and action plan for its development. Presently, as far as approach for development of Tourism in India is concerned, there are many areas which lack emphasis like inadequate awareness about tourist spots, no surveys and studies relating these tourists spots, no norms and standards for the planning and development of these tourist spots, neglect of heritage tourism, neglect of traditional arts, craft & culture, ineffective marketing, inadequate tourism infrastructure etc. In this paper an effort has been made to highlight the present scenario of Tourism in India and hurdles that comes in the way for the development of Sustainable Tourism and its related infrastructure. It further highlights the initiatives taken by the Government itself, for attracting foreign incentives and to encourage private sector as well to act as a facilitator by providing supportive infrastructure facilities.